A RELIABILITY APPROACH FROM MECHANICAL ENGINEERING POINT OF VIEW - Eker Gumus, Beril (YILDIZ TECHNICAL UNIV, 2018)
No mechanical product will perform reliably unless it is designed specifically for reliability. There are many studies about reliability in mechanical design but most of them focus on the one part of entire reliability problem. The ability to see the bigger picture is essential in the field of mechanical reliability. Reader can gain a holistic viewpoint for the consideration of mechanical reliability by this approach. In this study failure modes, reliability variables, models, measures and methods from mechanical engineering point of view were investigated. From the open literature, published research work was compiled. Search results were classified and evaluated in terms of suitability for mechanical engineering. As an example, the procedure to find the reliability of shaft was investigated in support of our approach. Analysis and documentation of failed mechanical components are essential for preventing designers from repeating the same errors. Therefore, this research is expected to provide an easy way to investigate reliability problems of mechanical components such as shafts.
Keywords: Mechanical reliability; failure modes; DESIGN; Engineering